ASSESSING THE VIEWS AND PERCEPTIONS OF WOMEN OF NAZARETH CHURCH REGARDING CERVICAL CANCER: A SURVEY IN UMLAZI SOUTH AFRICA. - Thembane, Nokukhanya; Jaya, Ziningi; Sibiya, Nelile (Student’s Journal of Health Research Africa, 2023)
Background: Cervical cancer is one of the leading causes of cancer-related death in women. The role of religious beliefs in shaping beliefs and practices in people has been proven. This research examines the views and perceptions of women in religious settings, with a specific focus on women from the Nazareth Church in Umlazi, in KwaZulu-Natal, in South Africa, regarding cervical cancer. The study aims to explore the role of religious groups in cervical cancer prevention and control. Methods: A qualitative survey questionnaire was used to collect data from a randomly selected sample of women from a Nazareth church in Umlazi, aged 18 years and above. The themes covered in the questionnaire included knowledge and awareness of cervical cancer, understanding of the disease, causes and risk factors, signs, and symptoms, curability, disease complications, participants’ knowledge sources, awareness of screening, and screening history. Results: Findings revealed a significant knowledge gap among the surveyed women, with a substantial proportion reporting limited awareness of cervical cancer. Understanding of the disease, its causes, and risk factors was found to be incomplete, highlighting the need for targeted educational interventions. Screening rates were low, indicating the importance of promoting cervical cancer screening and addressing barriers to screening uptake. Conclusion: Overall, the findings highlight the need for comprehensive educational campaigns, improved access to screening services, and targeted interventions to enhance knowledge, awareness, and uptake of cervical cancer prevention and screening measures among women. They also highlight the need for healthcare providers to collaborate with religious groups to develop targeted interventions and educational programs that align with religious beliefs and practices. Such efforts have the potential to enhance knowledge, awareness, and screening rates, and ultimately impact the burden of cervical cancer among women in South Africa, and potentially across the globe.